Insect Cold-Hardiness: Insights from the Arctic - Danks, H.V.; Kukal, Olga; Ring, R.A. (ARCTIC, 1994)
Cold-hardiness and related adaptations of insects in the Arctic correspond to characteristic climatic constraints. Some species are long-lived and are cold-hardy in several stages. In the Arctic, diapause and cold-hardiness are less likely to be linked than in temperate regions, because life-cycle timing depends as much on the need to coincide development with the short summer as on the need to resist winter cold. Winter habitats of many species are exposed rather than sheltered from cold so that development in spring can start earlier. Several features of cold-hardiness in arctic species differ from the characteristics of temperate species: these include very cold-hardy insects with low supercooling points that are not freezing tolerant; freezing-tolerant species that supercool considerably rather than freezing at relatively high subfreezing temperatures; mitochondrial degradation linked with the accumulation of cryoprotectants; and the possibly limited occurrence of thermal hysteresis proteins in winter. Several interesting relationships between cold-hardiness and water have been observed, including different types of dehydration. Winter mortality in arctic insects appear to be relatively low. Adaptations to cold in summer include retention of cold-hardiness, even freezing tolerance; selection of warm sites; and behaviour such as basking that allows elevated body temperatures. Studies especially on the high-arctic moth Gynaephora groenlandica show that various factors including cold-hardiness and other summer and winter constraints dictate the structure of energy budgets and the timing of life cycles. Future work should focus on the biological and climatic differences between arctic and other areas by addressing habitat conditions, life-cycle dynamics, and various aspects of cryoprotectant production at different times of year. Even in the Arctic cold-hardiness is complex and involves many simultaneous adaptations.Key words: cold-hardiness, insects, supercooling, freezing-tolerance, cryoprotectants, ...